IEMC 96 Proceedings. International Conference on Engineering and Technology Management. Managing Virtual Enterprises: A Converg
DOI: 10.1109/iemc.1996.547814
|View full text |Cite
|
Sign up to set email alerts
|

Identifying critical factors impacting virtual work group performance

Abstract: Virtual teams are an increasingly frequent response to the new competitive environment. Technological advances and global competition have moved virtual teaming from the "good idea I' stage to a critical strategy for many organizations. Our understanding of critical factors relative to virtual teams is limited us very few studies have been completed. Virtual teams are characterized as having high social complexity. Jointly optimizing the social and the technical organizational subsystems has been demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…Research comparing professional engineers to engineering students found that practiced professionals organized themselves as a group much more effectively than did the students (Smith & Leong, 1998). Professional engineers also communicated with each other throughout the process to ''stay on the same page,'' understand their failures, resolve disagreements and challenges, and reflect on their process (Hacker & Kleiner, 1996;Harvey & Koubek, 1998;Smith & Leong, 1998;Stempfle & Badke-Schaub, 2002). All of which takes some social skill.…”
Section: Engineering With Peoplementioning
confidence: 99%
See 2 more Smart Citations
“…Research comparing professional engineers to engineering students found that practiced professionals organized themselves as a group much more effectively than did the students (Smith & Leong, 1998). Professional engineers also communicated with each other throughout the process to ''stay on the same page,'' understand their failures, resolve disagreements and challenges, and reflect on their process (Hacker & Kleiner, 1996;Harvey & Koubek, 1998;Smith & Leong, 1998;Stempfle & Badke-Schaub, 2002). All of which takes some social skill.…”
Section: Engineering With Peoplementioning
confidence: 99%
“…Better solutions arise when diverse perspectives contribute to the creation of artifacts. Those who study collaboration and group work of engineering teams highlight how important interpersonal and social dynamics are to the process (Hacker & Kleiner, 1996;Hammond, Koubek, & Harvey, 2001;Stempfle & BadkeSchaub, 2002) and that the form of communication (inperson or virtually) within a design group matters (Harvey & Koubek, 1998). Stempfle and Badke-Schaub (2002) found that approximately 1/3 of the communication within a group designing collaboratively was aimed at structuring the group's process.…”
Section: Engineering With Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating the collaborative tools depends on many factors (Brown et al, 2007), where previous research works have been discussed the need to consider all different aspects that impacts the virtual teams performance (Hacker & Kleiner 1996;Wallace 1997;Nakayama & D´ávila, 2003). For our case and due the nature characteristics and needs of the virtual teams, the manufacturing process itself, the project's objectives, the current capabilities, and the intention to measure all steps in the process in order to look for the continuous process improvement.…”
Section: Evaluation and Selection Of The Collaborative Toolsmentioning
confidence: 99%
“…In this context, virtual teams require the use of information technology (IT) to exist, little is known about how the technology can be configured to optimize work group performance (Hacker & Kleiner, 1996). Although some of these aspects and concerns have been discussed before, in previous research works, more and diverse cases are need to support, design and establish a framework for best practices and lessons learned, that if the case, serve as a baseline to look for models, explore and develop standards based in a common standard-based foundation (Tomek, 2003), that in consequence will address common efforts of researches, developers, and practitioners dedicated to all different and diverse aspects of collaboration.…”
mentioning
confidence: 99%